2022
DOI: 10.3390/biom12020254
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aneurysm Tissue Neutrophil Mediator Levels with Intraluminal Thrombus Thickness in Patients with Abdominal Aortic Aneurysm

Abstract: An intraluminal thrombus (ILT), which accumulates large numbers of neutrophils, plays a key role in abdominal aortic aneurysm (AAA) pathogenesis. This study aimed to compare levels of selected neutrophil inflammatory mediators in thick and thin ILT, plus adjacent AAA walls, to determine whether levels depend on ILT thickness. Neutrophil mediator levels were analysed by enzyme-linked immunosorbent assays in thick and thin segments of ILT, plus adjacent aneurysm wall sections, taken from one aneurysm sac each fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Granulocyte, namely neutrophil (G0S2, PULA, FCGR3B) in this condition 35,36 , was the most abundant immune cell in IA. The high proportion of neutrophils (31.1%) was found even in the unruptured sample.…”
Section: Granulocytes In the Ia Tissuementioning
confidence: 72%
“…Granulocyte, namely neutrophil (G0S2, PULA, FCGR3B) in this condition 35,36 , was the most abundant immune cell in IA. The high proportion of neutrophils (31.1%) was found even in the unruptured sample.…”
Section: Granulocytes In the Ia Tissuementioning
confidence: 72%
“…However, the effect of MPO in larger AAAs appear to be controversial. Whereas Siennicka et al 22 observed a decrease in plasma MPO levels in patients with AAA, Zagrapan et al 23 reported an increase in this biomarker. These discrepancies between groups highlight the importance of further research into neutrophil biomarkers in AAA, as different AAA stages, inclusion criteria, and patient characteristics like comorbidities or medication may affect the levels of some of these molecules.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the thrombus causes a lack of wound healing in the aortic media, leading to increased aortic weakness and dilatation. 7 Whether antiplatelet and anticoagulant therapy affects aneurysmal dilatation and rupture is controversial. Currently, low-dose aspirin is recommended for patients with AAA, but the evidence is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ILT formation and growth are active and dynamic processes. 7 Evidence has shown that AAA rupture is a result of mechanical stress on the arterial wall. Some studies suggested that an increase in thrombus diameter might decrease mechanical stress as a mechanical cushion; therefore, preventing the aortic diameter from increasing.…”
Section: Introductionmentioning
confidence: 99%